PEMEROLEHAN POLA DASAR KALIMAT ANAK USIA 3;0-4;0 TAHUN (TINJAUAN PSIKOLINGUISTIK) SERTA IMPLIKASINYA TERHADAP KEMAMPUAN BERBAHASA ANAK USIA DINI (AUD) - Dwi Mutia Chan (Kantor Bahasa Kepulauan Riau, 2020)
The purpose of this study is to, (1) to describe the pattern of sentence children aged 3;0-4;0 years, (2) describe the form of speech children aged 3;0-4;0 years, (3) describe the form of implications for the development of language skills early childhood (AUD). This type of research is descriptive qualitative research method. based on the data analysis we can conclude the following matters as this. First, the sentence pattern diujarkan by children aged 3; 0-4; 0 years is. P (Predicate), S-P (Subject-Predicate), S-P-O-Pel (Subject-Predicate-Object-Complement) and S-P-O-Ket (Subject-Predicate-Object-Specification). Second, the form of speech children aged 3;0-4;0 year consists of speech one word, two words, three words, four words and five words. Third, the form of implications for the early childhood language skills.